2012
DOI: 10.3389/fnsys.2012.00060
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to sequence force perturbation during vertical and horizontal reaching movement—averaging the past or predicting the future?

Abstract: Several studies conducted during the past decade have suggested that episodic memory is better equipped to handle the future than the past. Here, we consider this premise in the context of motor memory. State-of-the-art computational models for trial-by-trial motor adaptation to constant and stochastic force field perturbations in a horizontal reaching paradigm have shown that motor memory registers a weighted sum of past experiences to predict force perturbation in a subsequent trial. In the current study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…Accordingly, MF control is largely based on estimates of the expected value of dynamics (Scheidt et al, 2001;Takahashi et al, 2001;Mawase and Karniel, 2012) without a safety margin. We thus designed a series of experiments to compare how the control of GFs and MFs is affected by environmental variability.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, MF control is largely based on estimates of the expected value of dynamics (Scheidt et al, 2001;Takahashi et al, 2001;Mawase and Karniel, 2012) without a safety margin. We thus designed a series of experiments to compare how the control of GFs and MFs is affected by environmental variability.…”
Section: Introductionmentioning
confidence: 99%
“…If the reaching speed would be quite different due to anticipation, then the perturbation applied by a velocity-dependent force field would differ across trials and participants as a result. Donchin and Shadmehr (2002) found participants were not able to learn random peak velocity force fields, another study also supported their findings (Mawase & Karniel, 2012). Therefore, using a distance-dependent force field, we ensured that all participants would experience the same peak sensorimotor perturbation, regardless of the reaching speed and added anticipatory information.…”
Section: Sensorimotor Adaptation Occurred Under Complex Force Fields 2mentioning
confidence: 57%
“…Force magnitudes could be another such variable, as it is related to the sensorimotor perturbation itself. Previous studies found participants were not able to adapt to randomly changing force magnitudes (Donchin & Shadmehr, 2002;Mawase & Karniel, 2012), so there may be limitations to this. A systematic study of different combinations of the two is needed.…”
Section: Implications and Future Directionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies showed that when exposed to novel load forces, manipulation and grip forces are adjusted in a different manner. Manipulation force control is mainly based on the estimation of the averaged external load forces [76,77]. In contrast, the predictive grip force control is highly sensitive to load variability [6], and is primarily operated to maintain a consistent GF/LF ratio with an additional safety margin to prevent slippage [22,23].…”
Section: Discussionmentioning
confidence: 99%